Species Diversity of Wild Mushroom at Sai Thong National Park, Chaiyaphum Province - Naksuwankul, Khwanyuruan; Saisong, Areerat; Sertsri, Orathai; Chotinate, Sutthiporn; Supama, Thantip; Niyanan, Fueanglada; Chanyang, Thanawan; Suwanwaree, Pongthep; Madang, Chom (KKU Science Journal, 2023)
The objective of this study is an investigation the species diversity of mushrooms in the forest at the conservation site in Sai Thong National Park, Chaiyaphum Province during the rainy season from June to August 2022. The Sai Thong National Park has comprised a diverse forest; dry dipterocarp, dry evergreen, lower montane rainforest, and secondary forest. In this national park, during rainy season, local peoples are permitted to access for collecting edible mushroom for their eating and selling in the local market. All samples were identified in laboratory on morphological characteristics. The results showed 15 families, 32 genera, and 66 taxa were observed in this area, the edible mushroom was found highest about 33 species and distribution in dry dipterocarp, dry evergreen, and lower montane rainforest. The medicinal mushroom was found in 5 species in dry dipterocarp forest only. The poisonous mushrooms were found in 13 species, the genus Amanita (6 species) presented the highest diversity and distribution in tree forest types. Based on the data of mushrooms diversify of edible and poisonous mushrooms obtained from the forest of Sai Thong National Park during the rainy season, should be notified or publicized for local villagers who come to collect mushrooms in the area in order to prevent collecting poisonous mushrooms for eating by people in the community.